Isokinetic Strength, Vertical Jump Performance, and Strength Differences in First Line Professional Firefighters Competing in Fire Sport - Miratsky, Petr; Gryc, Tomas; Cabell, Lee; Zahalka, Frantisek; Brozka, Matej; Varjan, Matej; Maly, Tomas (International journal of environmental research and public health, 2021)
The purpose of our study was to investigate peak torque (PT) of knee extensors (KE) and knee flexors (KF), bilateral and unilateral strength asymmetries in isokinetic testing and vertical jump height (JH), vertical ground reaction force (VGRF), and force differences (ΔVGRF) between legs during different jump tests in professional first-line firefighters (n = 15) competing in fire sports disciplines. There was a significant effect of jump type on JH (F2,44 = 7.23, p < 0.05), VGRF (F2,44 = 16.03, p < 0.05), and ΔVGRF (F2,44 = 3.45, p < 0.05). Professional firefighters achieved a mean JH of 50.17 cm in the countermovement jump free arms and high PT of KEs (3.15 Nm/kg). No significant differences (p > 0.05) and small effect sizes (d < 0.3) were found between the legs when PTs were assessed. We found a slightly higher (d = 0.53) unilateral strength ratio in non-dominant legs (58.12 ± 10.26%) compared to dominant legs (55.31 ± 7.51%). No effect of laterality was found among limb comparisons, but a higher unilateral isokinetic strength ratio was found in non-dominant legs of firefighters. A high level of strength (PT of KEs > 3 times body weight) and vertical jump performance is comparable to the performance of elite athletic populations.
Keywords: Firefighters; koleno; sporty; biomechanika; svalová síla; Biomechanical Phenomena; Muscle Strength; asymmetries; fire sport; performance; Humans; Sports; hasiči; tactical population; Knee; lidé